Pengaruh Lingkungan Kerja Dan Penerapan K3 Terhadap Rekonstruksi Ruas Jalan Tondon Kondo’ Toraja Utara - Luna, Yunus Sampe; Abduh, M. Natsir; Muliyani, Savitri Prasandi (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
In the reconstruction project in North Toraja Regency, occupational safety and health have been implemented, but there are some workers who do not comply with occupational safety and health regulations such as not wearing Personal Protective Equipment (helmets, vests, shoes, masks) while working, even though occupational safety and health facilities on this construction project have been available. In this study, we will analyze the variables that are considered important to study, namely Occupational Health and Safety and the work environment. This study uses a quantitative method, namely analyzing with the SPSS Program. From the results of the study, the Occupational Health and Safety Variable (X1) has a partial and simultaneous effect on the employee productivity variable (Y). The results of the T test are TX1 (3.759)> Ttable (2.05183) and the results of the F test are Fcount (12.951)> Ftable (3.34). The work environment variable (X2) has a partial and simultaneous effect on the employee productivity variable (Y) on the Tondon Kondo' Toraja Utara road reconstruction project. The results of the T test were TX1 (5.184) > Ttable (2.05183) and the results of the F test were Fcount (12.951) > Ftable (3.34).